Territorial marketing as a factor in attractiveness of investments - TAGHOUTI, Younes; DRIYASSE, Saleh; ABDELBAKI, Noureddine (Revue Internationale des Sciences de Gestion, 2024)
This paper explores the relationship between place branding and investment attractiveness, examining how strategic branding influences investment decisions and economic development. Using frameworks such as destination image theory and competitive identity, it integrates concepts like brand equity and stakeholder engagement. Through comparative case studies of cities like Dubai, Singapore, and Barcelona, the paper highlights successful branding strategies that have turned these locations into investment hubs. Data from academic literature, official reports, and branding campaigns provide insights into the role of clear, consistent, and authentic brand narratives in enhancing investment appeal by reinforcing positive perceptions and mitigating risks. The paper underscores the importance of aligning place branding with economic policy and stakeholder engagement, while addressing challenges such as balancing local identity with global appeal and adapting to trends like sustainability and digital transformation. It identifies the synergies between internal and foreign investment strategies, emphasizing authenticity in branding efforts. The research is limited to successful cities, which may affect its generalizability to other contexts. Future studies should examine more diverse locations to validate these findings. The paper provides practical guidance for policymakers and urban planners, bridging theory with real-world applications, and highlighting the evolving role of place branding in contemporary economic development.